Ciberurbanidade: interface e interação na cidade digital - Assis Junior, Fabio de Paula (2022)
The information and the language of the web change human cognition and modify mobility and physical boundaries. Thus, the Internet properly converts urban space and landscape into a cybernetic city. How, subsequently, does digital design production, via interface and interaction, participate in this phenomenon? The present research defends the thesis that the web transforms urban culture from technology not only as a creation tool, but as a language, defining a new concept of urbanity which is delimited in physical, mental and digital cities. In addition, it makes a comparative analysis between digital design and architecture and urbanism from the similarities and differences between the visual signs of the web and the cities. Their common elements are visualized in screens or facades interfaces, perceived in sitemaps or streets interactions, and felt as emotion in user or passerby experience. Finally, the thesis checks how the different visual and cognitive scales of the web update the urban culture